Poor Universal Coverage of Immediate Essential Newborn Care at Hospitals of Wollega Zones, The Case of Western Ethiopia - Kasaye HK; Yilma MT; Bobo FT; Fekadu G (Dove Medical Press, 2020)
Habtamu Kebebe Kasaye,1 Mekdes Tigistu Yilma,2 Firew Tekle Bobo,2,3 Ginenus Fekadu4 1Wollega University, Institute of Health Sciences, School of Nursing and Midwifery, Department of Midwifery, Nekemte, Ethiopia; 2Wollega University, Institute of Health Sciences, Department of Public Health, Nekemte, Ethiopia; 3Australian Centre for Public and Population Health Research, Faculty of Health, University of Technology Sydney, Sydney, New South Wales, Australia; 4Wollega University, Institute of Health Sciences, Department of Pharmacy, Nekemte, EthiopiaCorrespondence: Habtamu Kebebe Kasaye P.O. Box: 395, Nekemte, EthiopiaTel +251913426539Email habtamu@wollegauniversity.edu.etBackground: Thousands of neonates die annually in Ethiopia related to preventable causes. Low-quality care enhances neonatal morbidity and mortality unless remedial action is taken based on evidence. Here, we show the magnitude of essential newborn care service provisions and factors contributing to substandard care.Methods: We conducted a cross-sectional study in four hospitals of Wollega Zones from April to August 2017. We calculated 390 samples using Epi-info stat calc using necessary assumptions. A systematic random sampling method was used to select study participants. Non-participatory observations of essential newborn care service provisions were conducted using a World Health Organization checklist. We used binary logistic regression models to identify the independent predictors and reported variables having P-values less than 0.05 at 95% confidence intervals of odds ratios as significantly associated variables.Results: A total of 375 childbirths were observed and among these, only 11 (2.9%) neonates were given all components of immediate essential newborn care, while 315 (84.0%) of the newborns initiated early breast-feeding, 131 (34.9%) kept warm, 108 (28.8%) got disease prevention measures (89 (23.7%) helped to breathe, and only 14 (3.7%) kept clean immediately following the birth. Maternal highest annual income, maternal age, need of resuscitation, presence of assistant to a birth attendant, childbirth during the weekends were statistically significantly associated with immediate essential neonatal care categories in various predictive level.Conclusion: The essential newborn care provided for the neonates during childbirth at the health facilities was found to be poor. Continued efforts at improving access to quality essential newborn care provided for neonates are required. Hospital administrators need to consider enhancing the number of skilled delivery attendants, and enforcing implementations of essential newborn care standards is mandatory to protect the lives of neonates.Keywords: essential, newborn, care, Wollega, Ethiopia